The Use of Self-Estimated Aptitudes in Employment Counselling - Booth, J.A. Gordon; Laurin-Dumas, Monique S. (Canadian Journal of Counselling and Psychotherapy, 1980)
A study designed to determine if adults seeking employment under-estimated their aptitudes revealed that, although correlated, there are significant differences between self-estimated and measured aptitudes. It is concluded that the discrepancies between measured aptitudes and self-estimated aptitudes, which are a manifestation of one's self- concept, can be effectively challenged with the outcome being greater congruence between the person's self-structure and experience. The Rogerian model of the total personality is used to illustrate the potential of self-estimates when used in employment counselling to help clients reduce the state of stress often associated with employment seeking.